2007
DOI: 10.1111/j.1365-2354.2006.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Special considerations for haematology patients in relation to end-of-life care: Australian findings

Abstract: Recent hematology clinical guidelines recommend that palliative care specialists should have central roles in hemato-oncology teams. However, the available research evidence indicates there are presently significant obstacles to the integration of palliative care in hematology. The following discussion presents findings from an Australian study designed to address the problems associated with lack of referral of hematology patients to the palliative system through the development of a best-practice model for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 17 publications
2
51
0
Order By: Relevance
“…24,25 This makes it difficult to identify natural transitions to palliative goals of care. 26,27 In addition to these three primary findings, several other patient characteristics were identified that were independently associated with late hospice enrollment. These include male sex, comorbidities, and nonwhite ethnicity.…”
Section: Discussionmentioning
confidence: 95%
“…24,25 This makes it difficult to identify natural transitions to palliative goals of care. 26,27 In addition to these three primary findings, several other patient characteristics were identified that were independently associated with late hospice enrollment. These include male sex, comorbidities, and nonwhite ethnicity.…”
Section: Discussionmentioning
confidence: 95%
“…This is due to the nature of complications (sepsis and bleeding), variable treatment responses, the number of salvage therapies, unknown time to relapse, and not knowing which relapse will be the last. 45 Complications can also lead to the unexpectedly rapid deterioration in the patient's condition, 44,46 resulting in the transition occurring in a matter of hours. 47 This situation may mean that there is insufficient time for referral to palliative care or hospice services.…”
Section: Discussionmentioning
confidence: 98%
“…This objective has been achieved and the model developed is available both as a professional booklet [10] and in the peerreview literature [8,9,11,12]. The data from the study is rich and diverse covering a wealth of topics related to endof-life care in haematology.…”
Section: Methodsmentioning
confidence: 99%